Causes and Management of Insect and Mite Resistance in Strawberry Production - James F. Price; Curtis Nagle (EDIS)
Episodes of pest resistance to popular pesticides can cause yield losses, reduction of fruit quality, added control costs, environmental degradation, and emotional stress among farmers. These consequences can be alleviated if resistance management is practiced throughout the strawberry industry. If they minimize pesticide application by depending more on biological and cultural pest control measures, and take care not to expose pest populations to pesticides with identical modes of action, growers can avoid causing pesticide resistance. This 8-page fact sheet was written by James F. Price and Curtis Nagle and published by the UF Department of Entomology and Nematology, November 2012.